ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KOPI DI KABUPATEN TABANAN - I GUSTI AYU LIA YASMITA (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine the effect of capital, labor, land area variables on coffee production in Tabanan Regency. This type of research is a quantitative research, namely a study that aims to obtain evidence of a hypothesis. Data collection was carried out by means of interviews and questionnaires as well as direct observation. The sample used was 99 respondents with a simple random sampling technique (simple random sampling). In analyzing used multiple linear regression analysis techniques.The results showed that the partial regression coefficient test (t test) with α = 5% showed that the three variables (capital, labor and land area) had a positive and significant effect on coffee production in Tabanan Regency. The results of the F test with α = 5% show that together the variables of capital, labor and land area have a significant effect on coffee production in Tabanan Regency.